Assessment of Referral Patterns and Utilization of Basic Health Facilities in the Outpatient Department of a Tertiary Care Hospital: A Cross Sectional Study : Referral Patterns and Utilization of Basic Health Facilities - Kakakhel, Syed Ihtishaam; Mahmood, Humaira; Khan, Jawaria; Makey, Gul; Arif, Muhammad; Jamil, Sadaf; Habib, Farrukh; Raisani, Sher Afgan; Shaheen, Dure Yaqta; Diba, Farah (Pakistan Journal of Health Sciences, 2023)
The main reason behind poor healthcare delivery is malfunctioning of effective referral system. Objective: To determine the frequency of patients referred through proper channel in medical outpatient department of tertiary health care facility and to determine the causes of not utilizing basic health facilities by employing modified WHO questionnaire on Rapid Assessment of Referral Care System. A Cross-sectional descriptive study conducted in Medical Outpatient Department of Bacha Khan Medical Complex Swabi from 21st April to 21st September. Methods: Up to 400 participants going to medical outpatient department were selected through non-probability convenience sampling. Patient data like socio-demographic variables and questions with respect to referral was documented using a modified version of the Rapid Assessment of Referral Care System questionnaire from the World Health Organization. Percentages and frequencies were computed. Results: Amongst 400 participants who were included in the study, 244(61%) were female participants. About 365(91.3%) participants came to tertiary care hospital while (35) (8.8%) participants were referred. About 79(19.8%) participants were having chronic illness like Diabetes, hypertension, COPD, IHD, Asthma etc. 166(41.5%) participants choose this government facility due to presence of experienced doctors here in this facility. 159(39.8%) participants choose this facility due to presence of better care in this facility. Rest of them 75(18.7%) had other reasons. Conclusions: Most of the patients visited tertiary care hospital directly, with very minor health issues, not utilizing health facilities at the primary and secondary levels of care are overworked, which affects tertiary care facilities.